Hospital Mergers in Norway: Employee Health and Turnover to Three Destinations - Ingelsrud, Mari Holm (Nordic Journal of Working Life Studies, 2017)
This article investigates the probability of turnover to three destinations following hospital merg- ers: within the hospital sector, out of the hospital sector, and out of work. It is hypothesized that mergers increase turnover to nonemployment among employees with poor health and increase turnover to employment outside of the hospital sector among healthy employees. Discrete-time survival analyses show that mergers increase turnover within the hospital sector for all employ- ees, regardless of health. Turnover to other sectors and out of work does not increase. Possible explanations for the limited turnover out of the sector associated with mergers are aspects of the Norwegian labor market such as the institution of employee participation, low unemployment, and labor shortages within hospitals.